Missed Opportunities to Prescribe Preexposure Prophylaxis in South Carolina, 2013–2016. (22nd May 2018) - Smith, Dawn K; Chang, Man-Huei; Duffus, Wayne A; Okoye, Stella; Weissman, Sharon
Abstract : Healthcare visits by persons with indications for preexposure prophylaxis (PrEP) are not being adequately leveraged to address inequitably low PrEP use by black and Hispanic/Latino persons in the South, populations with high rates of new human immunodeficiency virus (HIV) diagnoses. Abstract: Background: Expanding use of preexposure prophylaxis (PrEP) in ways that address current racial/ethnic disparities is an important human immunodeficiency virus (HIV) prevention goal. We investigated missed opportunities to provide PrEP during healthcare visits that occur prior to HIV infection. Methods: This retrospective cohort study linked South Carolina HIV case surveillance data to 3 statewide healthcare databases. Characteristics of patients, healthcare visits and providers, sexually transmitted diseases (STDs), and other diagnoses were assessed for medical encounters occurring before an initial HIV diagnosis. Adjusted odds ratios were used to identify correlates of missed opportunities for PrEP provision. Results: Of 885 persons newly diagnosed during the study period, 586 (66%) had 4029 visits to a healthcare facility prior to their HIV diagnosis (mean of 6.9 visits) with missed opportunities for provision of PrEP. Emergency medicine–trained clinicians conducted (61%) and primary care clinicians (family practice or internal medicine) conducted 10% of visits. Also, 42% of visits were by persons who were uninsured or self-paid, 36% had public insurance, and 18% had commercial insurance. In multivariable analyses, being female, black, or aged <30 years were statistically significant predictors of having prior healthcare visits. Among persons with at least 1 healthcare visit prior to their HIV diagnosis, 28.5% had a diagnosis of gonorrhea, syphilis, or chlamydia at any visit. Conclusions: Healthcare visits occurring among persons who would benefit from provision of PrEP, especially persons with diagnosed STDs, should be leveraged to increase use of PrEP and reduce the risk of HIV acquisition.